Perempuan dan Kolonialisme: Pembacaan Feminisme Eksistensialis atas Karsa karya El Alicia - Auliya, Tasya Khilyatul; Safira, Rahmalia Putri; Widad, Madidatul (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2025)
In the facts of life, the existence of women has existed since the colonial period. Women voice their existence in society, as well as the existence of women in literary works. Female existentialism found in the novel “Karsa” by El Alicia is carried out by a character named Raden Ajeng Anjani. This research uses the theory of existentialism feminism pioneered by Simone de Beauvoir. This theory seeks to make women exist by themselves and have the right to choose their decisions as women. Similarly, El Alicia raised the theme of women in her work. This research uses a descriptive qualitative method by analyzing text data contained in the novel “Karsa,” the data collection technique used in this research is reading and recording. Observation in analyzing data is done by observing, reading and then recording data that is in accordance with the topic discussed. The results show that there are three efforts of women's existence made by Anjani's character, namely transforming in society, having an understanding that women have the right to gain insight, and wanting the existence of women to be valued. In addition, this study describes the marginalization of women as others, and the counter feminist characters in the novel “Karsa”.